Comprehensive design of steel structures - Punmia, B C; Jain, Ashok Kumar (Bangalore: Laxmi Publications (P) Ltd., 2017)
About the book: Design of Steel Structures is a comprehensive book on steel structures. The book comprises of chapters on riveted, bolted, pinned and welded connections, and bridges. This book is essential for civil engineering students and professionals.
Keywords: Civil Engineering; Steelwork connections; Beam Columns; Design of round tubular structures; Bridges; Timber structures